INEXPENSIVE PROTON EXCHANGE MEMBRANE SYNTHESIS BY SULFONATION OF COMMERCIALLY AVAILABLE POLYCARBONATE - Sherazi, T. A.; Siddique, N.; Kashmiri, M. A.; Ahmad, S. (The Nucleus, 2020)
Commercially available thermoplastic, bisphenol polymer (polycarbonate) was sulfonated with various reagents to introduce sulfonic acid group (SO3H) under optimum conditions. Subsequently modified polymer was studied for its physical and chemical properties needed for its potential use as PEM in Fuel Cells (FCs). Fourier Transform Infrared (FT-IR) and X-ray Diffraction (XRD) were performed to confirm the occurrence of sulfonation. Differential Thermal Analysis (DTA) and Themogravimetric Analysis (TGA) were used to determine the effects of sulfonation on glass transition temperature (Tg) and thermal stability of modified polymer. The Ion Exchange Capacity (IEC) and Degree of Substitution (DS) of sulfonic acid group were determined using standard procedure. Swelling properties were tested using water soaking. Scanning Electron Microscopy (SEM) was utilized to study the morphology of the polymeric membrane both before and after sulfonation. The results reveal that proper controlled sulfonation of bisphenol polymer can be a viable substitute for NAFION owing to its comparable IEC (1.15 meq/g), DS, water uptake (35%), good mechanical properties/ thermal stability and above all low cost of production.